Achieving industrial-grade purity in recycled copper scrap: Pretreatment and fire refining approach - Omar Choukri; Ezzine Mohsine; Souadi Taibi (Tribology and Materials)
As global demand for copper continues to grow, recycling has become a critical component of sustainable resource management. In 2022, recycled copper constituted 32 % of the total global consumption of this metal, significantly reducing the pressure on natural resources. Recycling between 40 and 65 % of copper scrap could significantly reduce the demand for primary metals, especially in regions with high industrial growth. Many studies have focused on purifying secondary copper and its scrap under specific conditions with expensive equipment, limiting their application in industrial environments. This study proposes an economical process, accessible to small foundries, based on pretreatment and fire refining around the copper's melting temperature of 1080 °C. Tested on three types of copper scrap samples, this process yielded satisfactory results, with copper purity approaching 4N (99.99 %) and a 23 % reduction in impurities. Additionally, the final product demonstrated excellent performance, exhibiting electrical conductivity exceeding 86 % IACS (International Annealed Copper Standard) and nearing 90 % IACS. This quality makes it suitable for various industrial applications according to certain standards. Therefore, this process will contribute to promoting the circular economy by optimising the valorisation of copper scrap and reducing the environmental footprint of its processing.